A magyar-jugoszláv határszakasz határköveinek története : 1921-1932 - Suba, János (Közép-Európai Közlemények, 2011)
Boundary signs are signs used to mark the state boundaries. The goal of fixing the borders with boundary signs is to make the border visible. Relationship between neighbouring countries is good if the regional coverage of the countries is unambiguous and known. This is why the border lines are fixed. Fixation can happen with descriptions, on maps, or ont he field with boundary-signs. The types and sizes of boundary signs were laid down by the Hungarian-Yugoslavian border establisher comittee. The types of the boundary signs are: triple landmark, numberes and not numbered elevation with wooden pale, wooden coloumns, numbered and not numbered landmarks. On the 631 km long border line, which is divided into 6 sections, in total 6088 pcs of boundary signs are placed. The first revision of boundary signs took place in 1932.